2020
DOI: 10.1186/s12883-020-01863-5
|View full text |Cite
|
Sign up to set email alerts
|

Medium- and long-term effects of endovascular treatments for severely stenotic basilar arteries supported by multimodal imaging

Abstract: Background: To evaluate the medium-and long-term effect of intravascular interventional therapy for symptomatic severe basilar artery stenosis supported by multimodal imaging. Method: After strict screening of 67 patients with symptomatic severe basilar artery stenosis (70-99%) with atherosclerotic stenosis, 67 patients with symptomatic recurrence after intensive drug treatment were treated with intravascular balloon dilatation and Enterprise stent implantation. Any stroke or death within 30 days after operati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It should be noted that TIA attributable to the target vessel was also recorded as the outcome, which may increase the event rate. Another two studies in China also used the Enterprise stent for symptomatic ICAS treatment, which yielded a successful operation rate of 100%, and the stroke or death rate within 30 days after the procedure was also low (12,19). However, the sample size of these two studies was small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that TIA attributable to the target vessel was also recorded as the outcome, which may increase the event rate. Another two studies in China also used the Enterprise stent for symptomatic ICAS treatment, which yielded a successful operation rate of 100%, and the stroke or death rate within 30 days after the procedure was also low (12,19). However, the sample size of these two studies was small.…”
Section: Discussionmentioning
confidence: 99%
“…On account of its advancement and release by a catheter system, the device may be used as an alternative to the wingspan system for treating ICAS. So far, several studies had reported the efficacies of the Enterprise stenting for ICAS, but few studies have focused on the long-term outcome in a high-volume stroke center (11,(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%